Generation of dislocation clusters by glide m‐planes in semipolar GaN layers. Issue 4 (20th March 2014) - Okada, N.; Ishikawa, A.; Yamane, K.; Tadatomo, K.; Jahn, U.; Grahn, H. T.
<x xml:space="preserve">Abstract</x> We prepared 11−22 GaN layers with different thicknesses on r‐plane patterned sapphire substrates (r‐PSS) through metal‐organic vapor phase epitaxy. In order to obtain a 11−22 GaN layer of high crystalline quality, a wide terrace was adopted for the r‐PSS according to the expansion of the laterally overgrown region. Using scanning electron microscopy and cathodoluminescence (CL) imaging, we observed that the defects are arranged along lines in certain directions and that their number increases with increasing thickness. These defects are expected to be dislocation clusters by CL measurement at 7 K. For the 11−22 GaN layer with anomalous defects (dark spots), the defects are arranged along a line tilted from the c‐axis of the GaN layer through a glide of the m‐plane in semipolar GaN, which is considered to be generated by the relaxation of the strained GaN layer.